Detection of pneumococcal DNA in blood by polymerase chain reaction for diagnosing pneumococcal pneumonia in young children From low- and middle-income countries - Morpeth, SC; Knoll, M; Scott, JAG; Park, DE; Watson, NL; Baggett, HC; Brooks, WA; Feikin, DR; Hammitt, LL; Howie, SRC; Kotloff, KL; Levine, OS; et al. (Oxford University Press, 2017)
Background We investigated the performance of polymerase chain reaction (PCR) on blood in the diagnosis of pneumococcal pneumonia among children from 7 low- and middle-income countries. Methods We tested blood by PCR for the pneumococcal autolysin gene in children aged 1–59 months in the Pneumonia Etiology Research for Child Health (PERCH) study. Children had World Health Organization–defined severe or very severe pneumonia or were age-frequency–matched community controls. Additionally, we tested blood from general pediatric admissions in Kilifi, Kenya, a PERCH site. The proportion PCR-positive was compared among cases with microbiologically confirmed pneumococcal pneumonia (MCPP), cases without a confirmed bacterial infection (nonconfirmed), cases confirmed for nonpneumococcal bacteria, and controls. Results In PERCH, 7.3% (n = 291/3995) of cases and 5.5% (n = 273/4987) of controls were blood pneumococcal PCR-positive (P < .001), compared with 64.3% (n = 36/56) of MCPP cases and 6.3% (n = 243/3832) of nonconfirmed cases (P < .001). Blood pneumococcal PCR positivity was higher in children from the 5 African countries (5.5%–11.5% among cases and 5.3%–10.2% among controls) than from the 2 Asian countries (1.3% and 1.0% among cases and 0.8% and 0.8% among controls). Among Kilifi general pediatric admissions, 3.9% (n = 274/6968) were PCR-positive, including 61.7% (n = 37/60) of those with positive blood cultures for pneumococcus. Discussion The utility of pneumococcal PCR on blood for diagnosing childhood pneumococcal pneumonia in the 7 low- and middle-income countries studied is limited by poor specificity and by poor sensitivity among MCPP cases.